Serum Levels of the Pro-Inflammatory cytokines IL-6 and TNF-alpha Vary Based on Diagnoses in Individuals with Low Back Pain. Issue 1 (April 2016) - Weber, Kathryn; Bloom, Ona; Quraishi, Shaheda; Overby, M. Chris; Levine, Mitchell; Chahine, Nadeen
Introduction: Many intervertebral disc diseases cause low back pain (LBP). Pro-inflammatory cytokines and matrix metalloproteinases (MMPs) participate in disc pathology. This study examines levels of serum cytokines and MMPs in human subjects with diagnosis of disc herniation (DH), spinal stenosis (SS) or degenerative disc disease (DDD) relative to levels in control subjects. Comparison between subjects with DH versus other diagnoses (Other Dx, grouped from SS and DDD) was performed to elaborate a pathological mechanism based on systemic cytokine levels. Material and Methods: Study participants were recruited from a spine neurosurgery practice ( n = 80), back pain management practice ( n = 27), or a control cohort ( n = 26). Serum samples were collected prior to treatment and were assayed by multiplex assays for levels of IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, IFN-γ, TNF-α, MMP-1, MMP-3 and MMP-9. Inflammatory and degradative mediator levels were compared between diagnosis and treatment groups. Multivariate regression for relationships with age, BMI, pain duration and smoking history were also performed. Results: Serum levels of IL-6 were significantly higher in LBP participants compared with controls. Participants with LBP due to Other Dx had significantly higher levels of IL-6 and TNF-α compared with DH and controls. Positive correlations were found between BMI and IL-6 levels, and TNF-α levels were positively correlated with age and BMI. Conclusion: The findings of the current clinical study are the first to examine systemic cytokine levels in DDD and SS and provide evidence for a more extensive role of IL-6 and TNF-α in disc diseases and LBP, where patients with DDD or SS have even higher serum cytokine levels compared with those with DH or control subjects. These findings may assist in refining personalized diagnosis using systemic biochemical profiling of disc diseases.